Current and promising therapies based on the pathogenesis of Graves’ ophthalmopathy - Zhang, Xin; Zhao, Qixiang; Li, Bei (Frontiers in Pharmacology, 2023)
Graves’ ophthalmopathy (GO) is a hyperthyroidism-related and immune-mediated disease that poses a significant threat to human health. The pathogenesis of GO primarily involves T cells, B cells, and fibroblasts, suggesting a pivotal role for the thyrotropin-antibody-immunocyte-fibroblast axis. Traditional treatment approaches for Graves’ disease (GD) or GO encompass antithyroid drugs (ATDs), radioactive iodine, and beta-blockers. However, despite decades of treatment, there has been limited improvement in the global incidence of GO. In recent years, promising therapies, including immunotherapy, have emerged as leading contenders, demonstrating substantial benefits in clinical trials by inhibiting the activation of immune cells like Th1 and B cells. Furthermore, the impact of diet, gut microbiota, and metabolites on GO regulation has been recognized, suggesting the potential of non-pharmaceutical interventions. Moreover, as traditional Chinese medicine (TCM) components have been extensively explored and have shown effective results in treating autoimmune diseases, remarkable progress has been achieved in managing GO with TCM. In this review, we elucidate the pathogenesis of GO, summarize current and prospective therapies for GO, and delve into the mechanisms and prospects of TCM in its treatment.